CUSTOMER COMPLAINT INFORMATION SYSTEM AT NATIONAL STANDARDIZATION AGENCY OF INDONESIA - Yuwan Jumaryadi (Bakti Nusantara Institute, 2019)
Technological developments changes the flow of information, where anyone can receive information easily. BSN as an Indonesian non-ministerial government institution needs to think about customer satisfaction with the services that provided. Completion of customer complaint is an important thing in fulfillment customer satisfaction. At present, the delivery of information regarding complaints against BSN services is still done in a conventional manner, where each user submits a complaint directly to the Helpdesk. However, in this case the section head is difficult to monitor every complaint that exists to improve the SLA. By proposing an Customer Complaint information system that can monitor customer complaints, it is hoped that it can improve service to any complaints that exist. This research is expected to assist users so that any complaints submitted can be resolved immediately, and are expected to increase SLA.